Simulation Model in Reducing Customer Waiting Time in Fast Food Drive-Thru System: A Case Study in Bangi - Abdul Basir, Nurashikin; R. Chandrashekar, (Research in Management of Technology and Business, 2020)
The demand of fast food supply is on the increasing trend especially in a society where consumers are busy working. Past researches have shown that most of the working populations are having too little time at home. Therefore, they are demanding a suitable product such as fast food that suits to their lifestyle. Waiting time theory or in other word queuing theory is originated from the mathematical theory that focuses in the waiting lines. This theory usually used and applied in service industry in customer waiting time in waiting lines. The purposes of study is to determine the optimum waiting line model in reducing customer-waiting time and identify the factors for a customer to be in waiting line for a long time period. There are two types of queuing theory that are single queue theory and multiple queue theory. In this research, multiple queue theory will be used to conduct the data collection with the quantitative method, where descriptive analysis is the main instrument used in data collection. The research conducted only in peak hour, which is at the lunch hour time period, from 12pm till 2pm. The data collected through questionnaire that will be analyzed by using Statistical Package for Social Science (SPSS) in order to get the mean score and the frequency of data. Furthermore, the observation and simulation model approach will be used in reducing the customer waiting time in McDonald’s restaurant.